Salib dan Imam Besar - Santoso, Audy (STT Reformed Injili Internasional, 2024)
A servant follows his master. Malchus, whose ear was cut off, followed the blind and deaf old high priest. The snake that is often depicted as Satan is an animal that does not have ears. Thus, the offspring of the serpent follow their father. When on the day of the resurrection of the Lord Jesus, these chief priests bribed the soldiers to lie about the events of the resurrection. Those fluent in the Torah violate the Torah, which clearly says that bribery blinds the eyes of those who see or are wise. One of the characteristics of those of us who serve the true high priest is the use of our ears. Christ said that the ears that hear are blessed.